Harmonization of Diversion Regulations In Juvenile Criminal Cases to Achieve Social Justice For Children In Conflict With The Law - Putri, Kartika; Susilawati, Endang (Indonesian Journal Publisher, 2025)
This research aims to examine the harmonization of diversion regulations within the juvenile criminal justice system in Indonesia as an effort to achieve social justice for children in conflict with the law. Diversi is a form of case resolution outside the criminal justice system that emphasizes a restorative justice approach. Although it has been regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA), the implementation of diversion still faces obstacles, particularly regarding the provision that limits diversion only to offenses with a maximum penalty of under seven years. This provision is considered not in line with the constitutional mandate and the principle of protecting children's human rights as stipulated in the 1945 Constitution and the Convention on the Rights of the Child. This research uses a normative juridical method with a descriptive-analytical approach. The research results indicate that there is a need for harmonization between the diversion provisions in the Child Protection System Law (UU SPPA) and other regulations to ensure more optimal protection of children's rights. This adjustment is important to prevent discrimination and trauma to children, as well as to realize a justice system that is oriented towards the best interests of the child.